Non-oriented magnetic steel sheet, iron core, manufacturing method of iron core, motor and manufacturing method of motor

JP2025028556APending Publication Date: 2025-03-03NIPPON STEEL CORPORATION

Patent Information

Application Number
JP2023133453
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2025-03-03

AI Technical Summary

Benefits of technology

【0011】 本発明の上記態様によれば、磁束密度、鉄損特性(商用周波鉄損および高周波鉄損)、並びに打ち抜き性に優れる無方向性電磁鋼板を提供することができ、加えて、この無方向性電磁鋼板を含む鉄心および鉄心の製造方法、並びに、この鉄心を含むモータおよびモータの製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025028556000001_ABST
    Figure 2025028556000001_ABST
Patent Text Reader

Abstract

To provide a non-oriented magnetic steel sheet excellent in magnetic flux density, iron loss characteristics and punchability, an iron core, a manufacturing method of an iron core, a motor and a manufacturing method of a motor.SOLUTION: In a non-oriented magnetic steel sheet, a base material steel sheet includes, as a chemical constitution, Si, Zn and Al. When the base material steel sheet is observed in a cross section with a cutting direction parallel to a board thickness direction, an average Zn concentration in a region from a surface of the base material steel sheet to a 1 / 10 board thickness is higher by 0.20 mass% or more in comparison to a Zn concentration of a 1 / 4 board thickness part, and is higher by 0.40 mass% or more in comparison to a Zn concentration of a 1 / 2 board thickness part.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a non-oriented electrical steel sheet, an iron core, a manufacturing method of an iron core, a motor, and a manufacturing method of a motor. More specifically, the present invention relates to a non-oriented electrical steel sheet having high magnetic flux density, excellent core loss characteristics, and excellent punchability, an iron core including this non-oriented electrical steel sheet, a manufacturing method of the iron core, and a motor including this iron core, and a manufacturing method of the motor. [Background technology]

[0002] Due to the need to reduce greenhouse gases, products that consume less energy are being developed in the industrial sector. For example, in the automotive sector, there are fuel-efficient vehicles such as hybrid vehicles that combine a gasoline engine and a motor, and electric vehicles that are driven by a motor. The common technology in these fuel-efficient vehicles is the motor, and miniaturizing and increasing the efficiency of motors are key technologies.

[0003] For example, there is a growing demand for miniaturization of drive motors for hybrid and electric vehicles due to space restrictions and the need to reduce fuel consumption through weight reduction. To miniaturize motors, it is necessary to increase the motor's torque. For this reason, there is a demand for further increasing the magnetic flux density of the non-oriented electrical steel sheets used as the iron core material for motors.

[0004] In addition, there is a limit to the battery capacity that can be installed in an automobile, so there is an increasing demand for high efficiency drive motors. To increase the efficiency of a motor, it is necessary to reduce energy loss. Therefore, there is a demand for further reduction in iron loss in non-oriented electrical steel sheets used as the iron core material of motors. In particular, in the motors of hybrid drive vehicles and electric vehicles, attempts are being made to increase the rotation speed of the motor to compensate for the decrease in torque that accompanies miniaturization. Therefore, there is a demand for non-oriented electrical steel sheets to further reduce iron loss from the commercial frequency range to the high frequency range.

[0005] In addition, the smaller the gap between the stator and rotor in the motor's internal structure, the better the motor's performance. Each component of the motor must have high shape precision. For this reason, the non-oriented electrical steel sheet used as the iron core material for the motor must also have excellent punching properties.

[0006] For example, Patent Document 1 discloses a silicon steel sheet having a higher Si concentration in the surface layer than in the center of the thickness of the steel sheet for the purpose of improving high-frequency iron loss, while Patent Document 2 discloses a non-oriented electrical steel sheet having an Al concentration gradient in the thickness direction for the purpose of improving high-frequency iron loss. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 11-293422 [Patent Document 2] International Publication No. 2009 / 072394 Summary of the Invention [Problem to be solved by the invention]

[0008] The techniques of Patent Documents 1 and 2 described above improve high-frequency iron loss to a certain extent. However, these techniques do not sufficiently take commercial-frequency iron loss into consideration. In addition, these techniques tend to reduce the punchability of the steel sheet due to the segregation of elements such as Si in the surface layer of the steel sheet, and do not sufficiently take into consideration the improvement of magnetic flux density.

[0009] The present invention has been made in view of the above problems. An object of the present invention is to provide a non-oriented electrical steel sheet that is excellent in magnetic flux density, iron loss characteristics (commercial frequency iron loss and high frequency iron loss), and punchability. Another object of the present invention is to provide an iron core including this non-oriented electrical steel sheet, a method for manufacturing the iron core, and a motor including this iron core, and a method for manufacturing the motor. [Means for solving the problem]

[0010] (1) A non-oriented electrical steel sheet according to one aspect of the present invention has The steel plate has a base material and an insulating coating. The base steel sheet has a chemical composition, in mass%, Si: 1.0% or more and 5.0% or less, Zn: 0.5% or more and 5.0% or less, Al: 1.0% or more and 6.0% or less, C: 0% or more and 0.0050% or less, Mn: 0% or more and 3.0% or less, P: 0% or more and 0.30% or less, S: 0% or more and 0.010% or less, N: 0% or more and 0.010% or less, Sn: 0% or more and 0.10% or less, Sb: 0% or more and 0.10% or less, Ca: 0% or more and 0.010% or less, Cr: 0% or more and 5.0% or less, Ni: 0% or more and 5.0% or less, Cu: 0% or more and 5.0% or less, Ce: 0% or more and 0.10% or less, B: 0% or more and 0.10% or less, O: 0% or more and 0.10% or less, Mg: 0% or more and 0.10% or less, Ti: 0% or more and 0.10% or less, V: 0% or more and 0.10% or less, Zr: 0% or more and 0.10% or less, Nd: 0% or more and 0.10% or less, Bi: 0% or more and 0.10% or less, W: 0% or more and 0.10% or less, Mo: 0% or more and 0.10% or less, Nb: 0% or more and 0.10% or less, Y: 0% or more and 0.10% or less, with the remainder being Fe and impurities, The thickness of the base steel plate is 0.10 mm or more and 0.35 mm or less, When the base steel plate is viewed on a cut surface whose cutting direction is parallel to the plate thickness direction, The average Zn concentration in the region from the surface of the base steel plate to 1 / 10 of the plate thickness is The Zn concentration is 0.20 mass% or more higher than the Zn concentration at 1 / 4 of the plate thickness, and The Zn concentration is 0.40 mass% or more higher than the Zn concentration at 1 / 2 the plate thickness. The Zn concentration at the quarter thickness portion is The Zn concentration is 0.20 mass% or more higher than the Zn concentration at the plate thickness 1 / 2 portion, The average Al concentration in the region from the surface to 1 / 10 of the plate thickness of the base steel plate is The Al concentration is 1.50 mass% or more higher than the Al concentration at 1 / 4 of the plate thickness, and The Al concentration is 3.0 mass% or more higher than the Al concentration at 1 / 2 the plate thickness. The Al concentration at the quarter thickness portion is The Al concentration is higher by 1.50 mass % or more than the Al concentration at the 1 / 2 plate thickness portion. (2) In the non-oriented electrical steel sheet described in (1) above, The base steel sheet has a chemical composition, in mass%, Cr: 0.50% or more and 2.0% or less, may also contain (3) An iron core according to an aspect of the present invention may include the non-oriented electrical steel sheet described in (1) or (2) above. (4) A method for producing an iron core according to one aspect of the present invention may include a step of laminating the non-oriented electrical steel sheets according to (1) or (2) above. (5) A motor according to an aspect of the present invention may include the iron core described in (3) above. (6) A method for manufacturing a motor according to one aspect of the present invention may include a step of laminating the non-oriented electrical steel sheets described in (1) or (2) above to obtain an iron core, and a step of assembling this iron core to obtain a motor. Effect of the Invention

[0011] According to the above aspects of the present invention, it is possible to provide a non-oriented electrical steel sheet that is excellent in magnetic flux density, iron loss characteristics (commercial frequency iron loss and high frequency iron loss) and punchability, and in addition to that, it is possible to provide an iron core including this non-oriented electrical steel sheet and a method for manufacturing the iron core, as well as a motor including this iron core and a method for manufacturing the motor. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a cross-sectional schematic diagram of a non-oriented electrical steel sheet according to an embodiment of the present invention. [Diagram 2] 1 is a flow diagram of a method for producing a non-oriented electrical steel sheet according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] A preferred embodiment of the present invention will be described in detail below. However, the present invention is not limited to the configuration disclosed in this embodiment, and various modifications are possible without departing from the spirit of the present invention. In addition, the numerical ranges described below include lower and upper limits. Numerical values ​​indicated as "greater than" or "less than" are not included in the numerical range. "%" regarding the content of each element means "mass %".

[0014] [Non-oriented electrical steel sheet] The inventors focused on Zn, which has not been considered in the prior art, and came up with the idea of ​​grading the Zn concentration in the thickness direction of the base steel sheet. Specifically, they thought that by providing a gradient in which the Zn concentration increases from the center of the sheet thickness toward the surface of the base steel sheet, it would be possible to improve the magnetic flux density, iron loss characteristics (commercial frequency iron loss and high frequency iron loss), and punchability.

[0015] In order to realize the above-mentioned Zn concentration gradient, it is considered difficult to control the concentration gradient if Zn is contained as a raw material of the base steel sheet from the steelmaking stage, but it is considered possible to control the concentration gradient by diffusing Zn into the base steel sheet at an intermediate stage of the manufacturing process. The present inventors have examined various process conditions for realizing the above-mentioned Zn concentration gradient. For example, they have attempted to diffuse Zn into the steel sheet by applying Zn plating to the steel sheet at an intermediate stage of the manufacturing process and then performing a heat treatment.

[0016] However, despite various investigations into plating conditions and heat treatment conditions, this method did not allow Zn to be favorably diffused into the steel sheet. The inventors considered that it would be difficult to diffuse Zn into the steel sheet using Zn alone, and attempted to diffuse Zn into the steel sheet in a composite manner by using other elements in combination. As a result, the inventors found that Zn could be favorably diffused into the steel sheet by applying a ZnAl alloy plating to the steel sheet instead of a Zn alone plating at an intermediate stage of the manufacturing process, and then controlling the diffusion heat treatment conditions.

[0017] Furthermore, the inventors produced steel sheets having various concentration gradients by changing the ZnAl alloy plating conditions and the diffusion heat treatment conditions, and evaluated the magnetic flux density, iron loss characteristics, and punchability of these steel sheets. As a result, the inventors found Zn concentration gradients and Al concentration gradients that can favorably improve the magnetic flux density, iron loss characteristics, and punchability.

[0018] As a result of the study by the inventors, it was found that by grading the Zn concentration in the thickness direction of the base steel sheet as described above, it is possible to improve the high-frequency iron loss without deteriorating the magnetic flux density, commercial frequency iron loss, and punchability. Although the effect of Zn diffusing into Fe on the resistivity of the steel sheet is not clear at present, it is estimated that Zn diffusing into Fe increases the resistivity of the steel sheet, although not as much as Si or Al, and as a result, it reduces the iron loss, mainly eddy current loss, when the skin effect, which becomes noticeable at high frequencies, is present. In addition to the Zn concentration, in this embodiment, the Al concentration is graded in the thickness direction of the base steel sheet, and it is estimated that this gradient of the Al concentration reduces the iron loss, mainly eddy current loss, when the skin effect, which becomes noticeable at high frequencies, is present.

[0019] When Si or Al diffuses into Fe, it causes crystal lattice distortion, inhibits domain wall motion, increases hysteresis loss, and also increases the hardness of the steel, degrading punchability. However, because Zn is a transition element like Fe, it causes only small crystal lattice distortion when diffused into Fe, and it is presumed that the inhibition of domain wall motion and the increase in steel hardness are suppressed compared to the diffusion of Al alone.

[0020] The non-oriented electrical steel sheet according to this embodiment, which has been completed based on the above findings, has the following features.

[0021] The non-oriented electrical steel sheet according to this embodiment includes a base steel sheet and an insulating coating, The base steel sheet has a chemical composition, in mass%, of: Si: 1.0% or more and 5.0% or less, Zn: 0.5% or more and 5.0% or less, Al: 1.0% or more and 6.0% or less, C: 0% or more and 0.0050% or less, Mn: 0% or more and 3.0% or less, P: 0% or more and 0.30% or less, S: 0% or more and 0.010% or less, N: 0% or more and 0.010% or less, Sn: 0% or more and 0.10% or less, Sb: 0% or more and 0.10% or less, Ca: 0% or more and 0.010% or less, Cr: 0% or more and 5.0% or less, Ni: 0% or more and 5.0% or less, Cu: 0% or more and 5.0% or less, Ce: 0% or more and 0.10% or less, B: 0% or more and 0.10% or less, O: 0% or more and 0.10% or less, Mg: 0% or more and 0.10% or less, Ti: 0% or more and 0.10% or less, V: 0% or more and 0.10% or less, Zr: 0% or more and 0.10% or less, Nd: 0% or more and 0.10% or less, Bi: 0% or more and 0.10% or less, W: 0% or more and 0.10% or less, Mo: 0% or more and 0.10% or less, Nb: 0% or more and 0.10% or less, Y: 0% or more and 0.10% or less, with the remainder being Fe and impurities, The thickness of the base steel plate is 0.10 mm or more and 0.35 mm or less, When the above-mentioned base steel plate is viewed on a cut surface with the cutting direction parallel to the plate thickness direction, The average Zn concentration in the region from the surface of the base steel plate to 1 / 10 of the plate thickness is The Zn concentration is 0.20 mass% or more higher than the Zn concentration at 1 / 4 of the plate thickness, and The Zn concentration is 0.40 mass% or more higher than the Zn concentration at 1 / 2 the plate thickness. The Zn concentration at the 1 / 4 part of the plate thickness is is higher by 0.20 mass% or more than the Zn concentration at the half thickness portion; The average Al concentration in the region from the surface of the base steel plate to 1 / 10 of the plate thickness is The Al concentration is 1.50 mass% or more higher than the Al concentration at 1 / 4 of the plate thickness, and The Al concentration is 3.0 mass% or more higher than the Al concentration at 1 / 2 the plate thickness. The Al concentration at the 1 / 4 part of the plate thickness is The Al concentration is 1.50 mass % or more higher than the Al concentration at the half plate thickness portion.

[0022] In addition, the non-oriented electrical steel sheet according to this embodiment has The base steel sheet has the chemical composition, in mass%, Cr: 0.5 or more and 2.0% or less, It is preferred that the compound contains

[0023] A cross-sectional schematic diagram of the non-oriented electrical steel sheet according to this embodiment is shown in Figure 1. Below, each feature of the non-oriented electrical steel sheet according to this embodiment will be described in detail.

[0024] Plate Thickness In the non-oriented electrical steel sheet according to this embodiment, the thickness of the base steel sheet is set to 0.35 mm or less, preferably 0.30 mm or less. On the other hand, since excessive thinning significantly reduces the productivity of the steel sheet and the motor, the thickness of the base steel sheet is set to 0.10 mm or more, preferably 0.15 mm or more.

[0025] The thickness of the base steel sheet may be measured with a micrometer. If the non-oriented electrical steel sheet to be measured has an insulating coating on its surface, the insulating coating is removed before the measurement. For example, the insulating coating may be removed by the following method.

[0026] A non-oriented electrical steel sheet having an insulating coating or the like is immersed in an aqueous solution of sodium hydroxide, an aqueous solution of sulfuric acid, and an aqueous solution of nitric acid in that order, and then washed. Finally, it is dried with hot air. In this way, a non-oriented electrical steel sheet (base steel sheet) from which the insulating coating has been removed can be obtained.

[0027] [Zn concentration gradient] In the non-oriented electrical steel sheet according to the present embodiment, when the base steel sheet is viewed on a cut surface parallel to the sheet thickness direction, the average Zn concentration in the region from the surface of the base steel sheet to 1 / 10 of the sheet thickness (surface region) is at least 0.20% by mass higher than the Zn concentration at 1 / 4 of the sheet thickness and at least 0.40% by mass higher than the Zn concentration at 1 / 2 of the sheet thickness. In order to favorably improve the magnetic flux density, iron loss characteristics, and punchability, the average Zn concentration in the surface region is preferably at least 0.25% by mass higher than the Zn concentration at 1 / 4 of the sheet thickness, and more preferably at least 0.3% by mass higher. Moreover, the average Zn concentration in the surface region is preferably at least 0.50% by mass higher than the Zn concentration at 1 / 2 of the sheet thickness, and more preferably at least 0.6% by mass higher.

[0028] Furthermore, in the non-oriented electrical steel sheet according to the present embodiment, when viewed from the above-mentioned cut surface, the Zn concentration at 1 / 4 of the sheet thickness may be at least 0.20 mass % higher than the Zn concentration at 1 / 2 of the sheet thickness. The Zn concentration at 1 / 4 of the sheet thickness is preferably at least 0.25 mass % higher, and more preferably at least 0.3 mass % higher, than the Zn concentration at 1 / 2 of the sheet thickness.

[0029] The average Zn concentration in the surface region, the Zn concentration in the 1 / 4 thickness portion, and the Zn concentration in the 1 / 2 thickness portion may satisfy the above relationship. Therefore, the Zn concentration in the surface region, the 1 / 4 thickness portion, and the 1 / 2 thickness portion as a chemical composition is not particularly limited. However, the Zn concentration in the 1 / 2 thickness portion where the Zn concentration in the cut surface is close to the minimum is preferably 0.050 mass% or more, more preferably 0.10 mass% or more, as a chemical composition. The Zn concentration in the 1 / 2 thickness portion is preferably 5.0 mass% or less, more preferably 4.0 mass% or less, and even more preferably 3.0 mass% or less, as a chemical composition. Similarly, the average Zn concentration in the surface region where the Zn concentration in the cut surface is close to the maximum is preferably 6.0 mass% or less, more preferably 5.0 mass% or less, and even more preferably 4.0 mass% or less, as a chemical composition. The average Zn concentration in the surface layer region, in terms of the chemical composition, is preferably 1.0 mass % or more, preferably 3.0 mass % or more, more preferably 3.3 mass % or more, and even more preferably 3.5 mass % or more.

[0030] The above-mentioned Zn concentration gradient can be confirmed by examining a cut surface parallel to the sheet thickness direction using an EPMA (Electron Probe Micro Analyzer).

[0031] Specifically, first, the insulating coating is removed from the non-oriented electrical steel sheet by the method described above to obtain a base steel sheet. A test piece is cut out from this base steel sheet so that the cutting direction is parallel to the sheet thickness direction. The cross-sectional structure of this cut surface is observed with an EPMA at a magnification that allows the sheet thickness of the base steel sheet to fit within the observation field. When the sheet thickness of the base steel sheet does not fit within the observation field, the cross-sectional structure is observed in multiple consecutive fields of view.

[0032] For the base steel plate in the above-mentioned observation field, a line analysis is performed in the plate thickness direction by EPMA to determine the average Zn concentration in the region from the surface of the base steel plate to 1 / 10 of the plate thickness (surface region), the Zn concentration at 1 / 4 plate thickness, and the Zn concentration at 1 / 2 plate thickness. The 1 / 2 plate thickness portion corresponds to the center portion in the plate thickness direction of the base steel plate on the above-mentioned cut surface, and the 1 / 4 plate thickness portion corresponds to the intermediate portion in the plate thickness direction between the surface and the 1 / 2 plate thickness portion on the above-mentioned cut surface. In the above linear analysis, the measurement line of the surface region, the measurement line of the 1 / 4 part of the plate thickness, and the measurement line of the 1 / 2 part of the plate thickness are assumed to overlap along the plate thickness direction. The average Zn concentration of the surface region is determined by analyzing the Zn concentration at equal intervals (e.g., 0.5 μm pitch) in the depth direction in the region from the surface of the base steel plate to 1 / 10 of the plate thickness, and the average value is defined as the "average Zn concentration of the region from the surface of the base steel plate to 1 / 10 of the plate thickness."

[0033] In the non-oriented electrical steel sheet according to the present embodiment, the cut surface is observed at any 10 observation points spaced apart from each other on the sheet surface, and the Zn concentration gradient satisfies the above condition at 7 or more of the observation points. If the Zn concentration gradient satisfies the above condition at 7 or more of the observation points, the magnetic flux density, iron loss characteristics, and punchability are preferably improved.

[0034] [Al concentration gradient] In the non-oriented electrical steel sheet according to the present embodiment, when the base steel sheet is viewed on a cut surface parallel to the sheet thickness direction, the average Al concentration in the region from the surface of the base steel sheet to 1 / 10 of the sheet thickness (surface layer region) is 1.50 mass% or more higher than the Al concentration at 1 / 4 of the sheet thickness and 3.0 mass% or more higher than the Al concentration at 1 / 2 of the sheet thickness. In order to favorably gradient the Zn concentration in the base steel sheet, the average Al concentration in the surface layer region is preferably 1.8 mass% or more higher, preferably 2.0 mass% or more higher, and more preferably 2.5 mass% or more higher than the Al concentration at 1 / 4 of the sheet thickness. In addition, the average Al concentration in the surface layer region is preferably 3.5 mass% or more higher, preferably 4.0 mass% or more higher, and more preferably 4.5 mass% or more higher than the Al concentration at 1 / 2 of the sheet thickness.

[0035] Furthermore, in the non-oriented electrical steel sheet according to the present embodiment, when viewed from the above-mentioned cut surface, the Al concentration at 1 / 4 of the sheet thickness may be at least 1.50 mass% higher than the Al concentration at 1 / 2 of the sheet thickness. The Al concentration at 1 / 4 of the sheet thickness is preferably at least 1.8 mass% higher, more preferably at least 2.0 mass% higher, and even more preferably at least 2.4 mass% higher than the Al concentration at 1 / 2 of the sheet thickness.

[0036] The average Al concentration in the surface region, the Al concentration in the 1 / 4 thickness portion, and the Al concentration in the 1 / 2 thickness portion may satisfy the above relationship. Therefore, the Al concentration in the surface region, the 1 / 4 thickness portion, and the 1 / 2 thickness portion as a chemical composition is not particularly limited. However, the average Al concentration in the surface region where the Al concentration is close to the maximum value in the cut surface is preferably 15 mass% or less, more preferably 12 mass% or less, and even more preferably 6.0 mass% or less, as a chemical composition. The average Al concentration in the surface region is preferably 3.0 mass% or more, more preferably 4.0 mass% or more, and even more preferably 5.0 mass% or more, as a chemical composition. Similarly, the Al concentration in the 1 / 2 thickness portion where the Al concentration is close to the minimum value in the cut surface is preferably 0.001 mass% or more, more preferably 0.01 mass% or more, and even more preferably 0.05 mass% or more, as a chemical composition. The Al concentration at the 1 / 2 plate thickness portion, as a chemical composition, is preferably 2.0 mass % or less, more preferably 1.0 mass % or less, and even more preferably 0.6 mass % or less.

[0037] The above-mentioned Al concentration gradient can be confirmed, similarly to the Zn concentration gradient, by examining a cut surface parallel to the sheet thickness direction using an EPMA (Electron Probe Micro Analyzer).

[0038] As with the Zn concentration gradient, in the non-oriented electrical steel sheet according to this embodiment, the above-mentioned cut surface is observed at any 10 observation locations spaced apart from each other on the sheet surface, and the Al concentration gradient satisfies the above condition at 7 or more observation locations. If the Al concentration gradient satisfies the above condition at 7 or more observation locations, the Zn concentration preferably has a gradient in the base steel sheet.

[0039] [Chemical composition] The non-oriented electrical steel sheet according to this embodiment is effective as long as the Zn concentration gradient and the Al concentration gradient are controlled as described above, so the chemical composition of the base steel sheet is not particularly limited. The base steel sheet may contain Si, Zn, and Al as a chemical composition, and may contain optional elements as necessary, with the balance being Fe and impurities. Each element will be described below. The chemical composition of the base steel sheet described below is the average value for the entire base steel sheet.

[0040] Si: 1.0% or more and 5.0% or less Silicon (Si) is an element that is effective in increasing the resistivity of steel sheet and reducing iron loss. Therefore, the Si content is set to 1.0% or more. The Si content is preferably 1.5% or more, and more preferably 2.0% or more. On the other hand, excessive inclusion of silicon significantly reduces the magnetic flux density. Therefore, the Si content is set to 5.0% or less. The Si content is preferably 4.0% or less, and more preferably 3.50% or less.

[0041] Zn: 0.5% or more and 5.0% or less Zn (zinc) is an element effective for improving magnetic flux density, core loss characteristics, and punchability. Therefore, the Zn content is set to 0.5% or more as an average of the entire base steel sheet. The Zn content is preferably 0.7%, and more preferably 1.0% or more. On the other hand, even if it is contained excessively, the above-mentioned effect is saturated. Therefore, the Zn content is set to 4.0% or less as an average of the entire base steel sheet. The Zn content is preferably 3.0% or less, and more preferably 2.5% or less. Zn may be included as a raw material of the base steel sheet from the steelmaking stage, but in order to control the Zn concentration gradient as described above, it is preferable to diffuse Zn into the base steel sheet at an intermediate stage of the manufacturing process.

[0042] Al: 1.0% or more and 6.0% or less Al (aluminum) is an element effective in grading the Zn concentration in the base steel sheet. Therefore, the Al content is set to 1.0% or more as an average of the entire base steel sheet. The Al content is preferably 1.5%, and more preferably 2.0% or more. On the other hand, even if excessively contained, the above effect is saturated. Therefore, the Al content is set to 6.0% or less as an average of the entire base steel sheet. The Al content is preferably 5.0% or less, and more preferably 4.0% or less. Note that Al may be included as a raw material of the base steel sheet from the steelmaking stage, but in order to control the Zn concentration gradient as described above, it is preferable to diffuse Al into the base steel sheet at an intermediate stage of the manufacturing process. Note that in this embodiment, Al means acid-soluble aluminum.

[0043] C: 0% or more and 0.0050% or less C (carbon) is an optional element. However, if it is contained in excess, the magnetic properties deteriorate. Therefore, the C content is set to 0.0050% or less. The C content is preferably 0.0030% or less. On the other hand, since it is preferable that the C content is low, there is no need to set a lower limit, and the lower limit may be 0%. However, since it is not easy to set the C content to 0% industrially, the lower limit may be set to more than 0%, or may be set to 0.0010%.

[0044] Mn: 0% or more and 3.0% or less Mn (manganese) is an optional element. Mn has the effect of increasing the resistivity of the steel sheet and reducing iron loss. However, since Mn has a higher alloying cost than Si and Al, a high Mn content is economically disadvantageous. For this reason, the Mn content is set to 3.0% or less, and preferably 2.50% or less. There is no need to limit the lower limit of Mn, and the lower limit may be 0%. However, in order to more reliably obtain the above effect, the Mn content is preferably more than 0%, preferably 0.0010% or more, and more preferably 0.010% or more.

[0045] P: 0% or more and 0.30% or less P (phosphorus) is an optional element. P has the effect of improving the texture of non-oriented electrical steel sheet and improving the magnetic properties. However, since P is also a solid solution strengthening element, if the P content is excessive, the steel sheet becomes hard and cold rolling becomes difficult. For this reason, the P content is set to 0.30% or less. The P content is preferably 0.20% or less. There is no need to limit the lower limit of P, and the lower limit may be 0%. However, in order to more reliably obtain the above effects, the P content is preferably more than 0%, preferably 0.0010% or more, and more preferably 0.0150% or more.

[0046] S: 0% or more and 0.010% or less S (sulfur) is an optional element. However, S combines with Mn in the steel to form fine MnS, which inhibits the growth of crystal grains during annealing and may deteriorate the magnetic properties of the non-oriented electrical steel sheet. For this reason, the S content is set to 0.010% or less. The S content is preferably 0.0050% or less, and more preferably 0.0030% or less. Since a small S content is preferable, there is no need to limit the lower limit, and the lower limit may be 0%. However, since it is not easy to industrially set the content to 0%, the lower limit may be set to more than 0% or may be set to 0.00010%.

[0047] N: 0% or more and 0.010% or less N (nitrogen) is an optional element. However, N combines with Al to form fine AlN, which may inhibit the growth of crystal grains during annealing and deteriorate the magnetic properties. For this reason, the N content is set to 0.010% or less. The N content is preferably 0.0050% or less, and more preferably 0.0030% or less. Since it is preferable that the N content is low, there is no need to limit the lower limit, and the lower limit may be 0%. However, since it is not easy to industrially set the content to 0%, the lower limit may be more than 0%, may be 0.00010% or more, may be more than 0.00150%, or may be 0.00250% or more.

[0048] Sn: 0% or more and 0.10% or less Sb: 0% or more and 0.10% or less Sn (tin) and Sb (antimony) are optional elements. Sn and Sb have the effect of improving the texture of the non-oriented electrical steel sheet and improving the magnetic properties (for example, magnetic flux density). However, excessive inclusion of these elements may embrittle the steel, causing cold rolling fracture, and may also deteriorate the magnetic properties. For this reason, the contents of Sn and Sb are each set to 0.10% or less. There is no need to limit the lower limit of Sn and Sb, and the lower limit may be 0%. However, in order to obtain the above effect more reliably, the Sn content is preferably more than 0%, preferably 0.0010% or more, and more preferably 0.010% or more. In addition, the Sb content is preferably more than 0%, preferably 0.0010% or more, preferably 0.0020% or more, more preferably 0.010% or more, and more preferably more than 0.0250%.

[0049] Ca: 0% or more and 0.010% or less Ca (calcium) is an optional element. Ca suppresses the precipitation of fine sulfides (MnS, Cu2S, etc.) by generating coarse sulfides, so it is effective in inclusion control. When Ca is added in an appropriate amount, it has the effect of improving the crystal grain growth and improving magnetic properties (for example, iron loss). However, if it is contained in an excessive amount, the above effect saturates and leads to an increase in cost. Therefore, the Ca content is set to 0.010% or less. The Ca content is preferably 0.0080% or less, and more preferably 0.0050% or less. There is no need to limit the lower limit of Ca, and the lower limit may be 0%. However, in order to obtain the above effect more reliably, the Ca content is preferably more than 0%, and is preferably 0.00030% or more. The Ca content is preferably 0.0010% or more, and more preferably 0.0030% or more.

[0050] Cr: 0% or more and 5.0% or less Cr (chromium) is an optional element. Cr has the effect of increasing resistivity and improving magnetic properties (for example, iron loss). However, if it is contained in excess, it may reduce the saturation magnetic flux density, and the above effect will saturate, leading to an increase in costs. Therefore, the Cr content is set to 5.0% or less. The Cr content is preferably 2.0% or less, and more preferably 1.0% or less. There is no need to limit the lower limit of Cr, and the lower limit may be 0%. However, in order to obtain the above effect more reliably, the Cr content is preferably more than 0%, and is preferably 0.0010% or more. In addition, Cr suppresses the formation of Kirkendall voids when Zn or Al is diffused into the base steel sheet. Therefore, the Cr content is preferably 0.50% or more.

[0051] Ni: 0% or more and 5.0% or less Ni (nickel) is an optional element. Ni has the effect of improving magnetic properties (e.g., saturation magnetic flux density). However, if excessively contained, the above effect saturates, resulting in increased costs. Therefore, the Ni content is set to 5.0% or less. The Ni content is preferably 0.50% or less, and more preferably 0.10% or less. There is no need to set a lower limit for Ni, and the lower limit may be 0%. However, in order to obtain the above effect more reliably, the Ni content is preferably more than 0%, and is preferably 0.0010% or more.

[0052] Cu: 0% or more and 5.0% or less Cu (copper) is an optional element. Cu has the effect of improving the strength of the steel sheet. However, excessive Cu content may decrease the saturation magnetic flux density, and the above effect may saturate, resulting in an increase in costs. Therefore, the Cu content is set to 5.0% or less. The Cu content is preferably 0.10% or less. There is no need to set a lower limit for Cu, and the lower limit may be 0%. However, in order to more reliably obtain the above effect, the Cu content is preferably more than 0%, and is preferably 0.0010% or more.

[0053] Ce: 0% or more and 0.10% or less Ce (cerium) is an optional element. Ce has the effect of suppressing the precipitation of fine sulfides (MnS, Cu2S, etc.) by generating coarse sulfides and oxysulfides, improving grain growth, and reducing iron loss. However, if it is contained in excess, oxides are also generated in addition to sulfides and oxysulfides, which may deteriorate iron loss, and the above effect will saturate and lead to an increase in costs. Therefore, the Ce content is set to 0.10% or less. The Ce content is preferably 0.010% or less, more preferably 0.0090% or less, and even more preferably 0.0080% or less. There is no need to limit the lower limit of Ce, and the lower limit may be 0%. However, in order to obtain the above effect more reliably, the Ce content is preferably more than 0%, and is preferably 0.0010% or more. The Ce content is more preferably 0.0020% or more, even more preferably 0.0030% or more, and even more preferably 0.0050% or more.

[0054] The chemical composition of the base steel sheet of the non-oriented electrical steel sheet according to this embodiment may contain, in addition to the above elements, optional elements such as B, O, Mg, Ti, V, Zr, Nd, Bi, W, Mo, Nb, and Y. The contents of these optional elements may be controlled based on known knowledge. For example, the contents of these optional elements may be as follows. The lower limit of these optional elements may be more than 0%. B: 0% or more and 0.10% or less, O: 0% or more and 0.10% or less, Mg: 0% or more and 0.10% or less, Ti: 0% or more and 0.10% or less, V: 0% or more and 0.10% or less, Zr: 0% or more and 0.10% or less, Nd: 0% or more and 0.10% or less, Bi: 0% or more and 0.10% or less, W: 0% or more and 0.10% or less, Mo: 0% or more and 0.10% or less, Nb: 0% or more and 0.10% or less, Y: 0% or more and 0.10% or less.

[0055] In addition, the base steel sheet of the non-oriented electrical steel sheet according to this embodiment has a chemical composition, in mass%, C: 0.0010% or more and 0.0050% or less, Mn: 0.0010% or more and 3.0% or less, P: 0.0010% or more and 0.30% or less, S: 0.00010% or more and 0.010% or less, N: more than 0.00150% and less than 0.010%, B: 0.00010% or more and 0.10% or less, O: 0.00010% or more and 0.10% or less, Mg: 0.00010% or more and 0.10% or less, Ca: 0.00030% or more and 0.010% or less, Ti: 0.00010% or more and 0.10% or less, V: 0.00010% or more and 0.10% or less, Cr: 0.0010% or more and 5.0% or less, Ni: 0.0010% or more and 5.0% or less, Cu: 0.0010% or more and 5.0% or less, Zr: 0.00020% or more and 0.10% or less, Sn: 0.0010% or more and 0.10% or less, Sb: 0.0010% or more and 0.10% or less, Ce: 0.0010% or more and 0.10% or less, Nd: 0.0020% or more and 0.10% or less, Bi: 0.0020% or more and 0.10% or less, W: 0.0020% or more and 0.10% or less, Mo: 0.0020% or more and 0.10% or less, Nb: 0.00010% or more and 0.10% or less, Y: 0.0020% or more and 0.10% or less, It is preferable that the compound contains at least one of the above.

[0056] Also, the B content is preferably 0.010% or less, the O content is preferably 0.010% or less, the Mg content is preferably 0.0050% or less, the Ti content is preferably 0.0020% or less, the V content is preferably 0.0020% or less, the Zr content is preferably 0.0020% or less, the Nd content is preferably 0.010% or less, the Bi content is preferably 0.010% or less, the W content is preferably 0.010% or less, the Mo content is preferably 0.01% or less, the Nb content is preferably 0.0020% or less, and the Y content is preferably 0.010% or less. Also, the Ti content is preferably 0.0010% or more, the V content is preferably 0.0020% or more, and the Nb content is preferably 0.0020% or more.

[0057] The above-mentioned chemical composition may be measured by a general analysis method for steel. For example, the chemical composition may be measured by ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). Al may be measured as acid-soluble Al by ICP-AES using the filtrate obtained by thermally decomposing a sample with acid. C and S may be measured by the combustion-infrared absorption method, N by the inert gas fusion-thermal conductivity method, and O by the inert gas fusion-non-dispersive infrared absorption method.

[0058] In the non-oriented electrical steel sheet according to the present embodiment, the crystal grain size of the base steel sheet is not particularly limited, but for example, the crystal grain size is preferably 40 μm or more and 200 μm or less on average. The average crystal grain size of the base steel sheet is preferably 60 μm or more, and more preferably 80 μm or more. On the other hand, the average crystal grain size of the base steel sheet is preferably 150 μm or less, and more preferably 120 μm or less.

[0059] The average grain size may be measured by the intercept method specified in JIS G0551:2020. For example, the average grain size measured by the intercept method in the plate thickness direction and the rolling direction in a longitudinal section structure photograph may be used. As the longitudinal section structure photograph, an optical microscope photograph may be used, and for example, a photograph taken at a magnification of 50 times may be used.

[0060] [Manufacturing method of non-oriented electrical steel sheets] An example of a method for manufacturing the non-oriented electrical steel sheet according to the present embodiment will be described below. Note that the manufacturing method of the non-oriented electrical steel sheet according to the present embodiment is not particularly limited as long as it has the above-mentioned configuration. The manufacturing method described below is one example for manufacturing the non-oriented electrical steel sheet according to the present embodiment, and is a suitable example of the method for manufacturing the non-oriented electrical steel sheet according to the present embodiment.

[0061] For example, the manufacturing method of the non-oriented electrical steel sheet according to the present embodiment may include a casting step, a hot rolling step, a cold rolling step, a surface treatment step, and a finish annealing step. The surface treatment step is a step of plating a ZnAl alloy on the surface of the steel sheet, and may be carried out, for example, after the hot rolling step or the cold rolling step. The finish annealing step is generally a step of controlling the recrystallization and grain size of steel, but in the present embodiment, it also serves as a heat treatment for diffusing the ZnAl alloy into the steel sheet.

[0062] Specifically, the method for producing the non-oriented electrical steel sheet according to this embodiment includes the steps of: The method includes a casting process, a hot rolling process, a cold rolling process, a surface treatment process, and a finish annealing process. In the casting process, the chemical composition is, in mass%, Si: 1.0% or more and 5.0% or less, Zn: 0% or more and 0.10% or less, Al: 0% or more and 0.6% or less, C: 0% or more and 0.0050% or less, Mn: 0% or more and 3.0% or less, P: 0% or more and 0.30% or less, S: 0% or more and 0.010% or less, N: 0% or more and 0.010% or less, Sn: 0% or more and 0.10% or less, Sb: 0% or more and 0.10% or less, Ca: 0% or more and 0.010% or less, Cr: 0% or more and 5.0% or less, Ni: 0% or more and 5.0% or less, Cu: 0% or more and 5.0% or less, Ce: 0% or more and 0.10% or less, B: 0% or more and 0.10% or less, O: 0% or more and 0.10% or less, Mg: 0% or more and 0.10% or less, Ti: 0% or more and 0.10% or less, V: 0% or more and 0.10% or less, Zr: 0% or more and 0.10% or less, Nd: 0% or more and 0.10% or less, Bi: 0% or more and 0.10% or less, W: 0% or more and 0.10% or less, Mo: 0% or more and 0.10% or less, Nb: 0% or more and 0.10% or less, Y: 0% or more and 0.10% or less, and the balance being Fe and impurities, In the hot rolling step, the slab is hot rolled, In the cold rolling step, the steel sheet is subjected to cold rolling, In the surface treatment step, a ZnAl alloy containing 50% by mass or more and 80% by mass or less of Al with the remainder being Zn and impurities is plated on the surface of the steel sheet to a thickness of 3 μm or more and 35 μm or less, In the above-mentioned finish annealing process, In the oxidation process, the ZnAl alloy-plated steel sheet is heated from room temperature to a temperature range of 200°C to 500°C in an atmosphere with a dew point of more than 0°C and less than 20°C. In the heating process, the steel sheet after the oxidation process is heated to a temperature range of 1000°C to 1200°C in an atmosphere of 95% by volume to 100% by volume hydrogen with a dew point of -50°C to 0°C in a heating time of 1 second to 15 hours, and then held in the temperature range of 1000°C to 1200°C for a time of 0 minutes to less than 1 minute, In the soaking process, the steel sheet after the heating process is cooled to a temperature range of 800°C to 1100°C, and then soaked at the temperature range of 800°C to 1100°C for 1 minute to 20 hours. In the cooling process, the steel sheet after the soaking process may be cooled to a temperature range of room temperature or higher and 400° C. or lower at an average cooling rate of 0.1° C. / min to 10° C. / min. The above room temperature corresponds to the "normal temperature" defined in JIS Z 8703:1983, and means a range of 20±15°C (5 to 35°C).

[0063] The method for producing a non-oriented electrical steel sheet according to the present embodiment may further include a hot-rolled sheet annealing step after the hot rolling step. The method for producing a non-oriented electrical steel sheet according to the present embodiment may further include a pickling step after the hot rolling step or the hot-rolled sheet annealing step. The method for producing a non-oriented electrical steel sheet according to the present embodiment may further include a coating formation step after the finish annealing step.

[0064] A flow chart of the method for producing a non-oriented electrical steel sheet according to this embodiment is shown in Figure 2. Each step will be described in detail below.

[0065] [Casting process] In the casting process, a slab (steel billet) having the above-mentioned chemical composition is cast. The chemical composition of the slab is substantially the same as that of the base steel sheet of the non-oriented electrical steel sheet, except for Zn and Al. Zn and Al are plated on the steel sheet as a ZnAl alloy in the surface treatment process, and are diffused into the steel sheet in the finish annealing process. Therefore, in this embodiment, the Zn and Al contents are different between the slab and the final product.

[0066] The casting method is not particularly limited, but for example, a slab may be produced by a continuous casting method, or an ingot may be produced by using molten steel and then blooming the ingot to produce a slab. Alternatively, a slab may be produced by other methods.

[0067] The thickness of the slab is not particularly limited, but may be, for example, 150 mm or more and 350 mm or less. The thickness of the slab is preferably 220 mm or more and 280 mm or less. As the slab, a so-called thin slab having a thickness of 10 mm or more and 70 mm or less may be used.

[0068] [Hot rolling process] In the hot rolling process, the slab is hot rolled to obtain a hot rolled steel sheet. The hot rolling conditions are not particularly limited, but for example, the thickness (finishing thickness) of the hot rolled steel sheet is preferably 1.0 mm or more and 2.5 mm or less. If the thickness is 1.0 mm or more, the load on the hot rolling machine is small, and the productivity in the hot rolling process is high.

[0069] The heating temperature of the slab before hot rolling is not particularly limited, but may be 1000° C. or more and 1300° C. or less from the viewpoint of costs, etc. In the finish hot rolling after the rough rolling, the final rolling temperature of the finish hot rolling is preferably 900° C. or more, and more preferably 950° C. or more.

[0070] [Cold rolling process] In the cold rolling process, the steel sheet is cold-rolled to obtain a cold-rolled steel sheet. In the cold rolling process, the thickness (finishing thickness) of the cold-rolled steel sheet may be 0.10 mm or more and 0.35 mm or less. The steel sheet to be cold-rolled may be any of a steel sheet after a hot rolling process, a steel sheet after a hot-rolled sheet annealing process, a steel sheet after a pickling process, and a steel sheet after a surface treatment process.

[0071] Other cold rolling conditions are not particularly limited, but for example, the cumulative reduction in cold rolling is preferably 60% to 95%. When the reduction is 60% or more, the effect of P on the texture of the non-oriented electrical steel sheet can be more stably obtained. Also, when the reduction is 95% or less, the non-oriented electrical steel sheet can be stably produced on an industrial scale.

[0072] The temperature of the steel sheet during cold rolling may be room temperature. Alternatively, the cold rolling may be warm rolling in which the steel sheet temperature is 100° C. to 200° C. In order to heat the steel sheet to a temperature of 100° C. to 200° C., the steel sheet may be preheated or the rolls may be preheated.

[0073] [Surface treatment process] In the surface treatment step, a ZnAl alloy containing 50% by mass or more and 80% by mass or less of Al with the remainder being Zn and impurities may be plated on the surface of the steel sheet to a thickness of 3 μm or more and 35 μm or less. The steel sheet to be surface treated may be any of a steel sheet after a hot rolling step, a steel sheet after a hot-rolled sheet annealing step, a steel sheet after a pickling step, and a steel sheet after a cold rolling step.

[0074] The Al content of the ZnAl alloy plated on the surface of the steel sheet is preferably 55 mass% or more, more preferably 60 mass% or more, while the Al content is preferably 75 mass% or less, more preferably 70 mass% or less.

[0075] In addition, the thickness of the ZnAl alloy plated on the surface of the steel sheet is preferably 5 μm or more, more preferably 7 μm or more. On the other hand, this thickness is preferably 30 μm or less, more preferably 25 μm or less. When the ZnAl alloy is plated before cold rolling, the thickness of the ZnAl alloy is reduced to about 1 / 5 by cold rolling, so it is preferable to set the thickness taking into account the reduction in thickness by cold rolling. For example, it is preferable to set the thickness to 25 μm or more and 35 μm or less within the above-mentioned numerical range.

[0076] The method for plating the surface of the steel sheet with a ZnAl alloy is not particularly limited, but may be, for example, hot-dip plating, electroplating, molten salt electrolysis, PVD (Physical Vapor Deposition), or CVD (Chemical Vapor Deposition). Among these, hot-dip plating is preferred in consideration of the fact that the material is for motors and the processing costs.

[0077] [Finishing annealing process] In the final annealing process, the ZnAl alloy-plated steel sheet is subjected to an oxidation process, a temperature increase process, a soaking process, and a cooling process, which recrystallize the steel, grow the crystal grains to a desired grain size, and diffuse the ZnAl alloy into the steel sheet.

[0078] [Oxidation process] In the oxidation process of the final annealing step, the ZnAl alloy-plated steel sheet may be heated from room temperature to a temperature range of 200° C. or more and 500° C. or less in an atmosphere with a dew point of more than 0° C. and not more than 20° C. Note that the steel sheet subjected to the oxidation process may be either a steel sheet after a cold rolling process or a steel sheet after a surface treatment process.

[0079] The dew point of the atmosphere in the oxidation process is preferably 5° C. or higher, and more preferably 8° C. or higher. On the other hand, this dew point is preferably 15° C. or lower, and more preferably 12° C. or lower. The temperature range to which the temperature rises in the oxidation process is preferably 250° C. or higher, and more preferably 270° C. or higher. On the other hand, this temperature range is preferably 450° C. or lower, and more preferably 400° C. or lower.

[0080] It is believed that the above-mentioned oxidation process forms an Al oxide film on the surface of the ZnAl alloy, which suppresses the evaporation of Zn during the post-treatment heating and soaking processes, and as a result, a Zn concentration gradient can be achieved in the base steel sheet.

[0081] The above-mentioned oxidation process is necessary when the Zn content of the ZnAl alloy plated on the steel sheet exceeds 10%. If the above-mentioned oxidation process is carried out when the Zn content of the ZnAl alloy plated on the steel sheet is 10% or less, the magnetic properties will deteriorate.

[0082] [Temperature rise process] In the temperature-raising process of the final annealing process, the steel sheet after the oxidation process is heated to a temperature range of 1000°C or more and 1200°C or less in an atmosphere of 95% by volume or more and 100% by volume or less with a dew point of -50°C or more and 0°C or less in a temperature-raising time of 1 second or more and 15 hours or less, and then held in the temperature range of 1000°C or more and 1200°C or less for a time of 0 minutes or more and less than 1 minute.

[0083] The hydrogen in the atmosphere during the temperature rise process is preferably 96% by volume or more, and more preferably 97% by volume or more. On the other hand, this hydrogen is preferably 99% by volume or less, and more preferably 98% by volume or less. The dew point of the atmosphere during the temperature rise process is preferably -40°C or more, and more preferably -30°C or more. On the other hand, this dew point is preferably -10°C or less, and more preferably -20°C or less. The temperature range to which the temperature rises during the temperature rise process is preferably 1050°C or more, and more preferably 1100°C or more. On the other hand, this temperature range is preferably 1150°C or less, and more preferably 1130°C or less. The temperature range to which the temperature rises during the temperature rise process is preferably the same as the temperature range to be held during the temperature rise process. The holding time is preferably 1 second or more, and more preferably 10 seconds or more. On the other hand, this holding time is preferably 50 seconds or less, and more preferably 30 seconds or less.

[0084] It is believed that the above-mentioned temperature rise process causes Zn to diffuse from the ZnAl alloy to the base steel sheet, increasing the Zn concentration in the surface layer region of the base steel sheet.

[0085] [Soaking process] In the soaking process of the final annealing step, the steel sheet after the heating process is cooled to a temperature range of 800°C to 1100°C and then soaked in the temperature range of 800°C to 1100°C for 1 minute to 20 hours. The soaking temperature in the soaking process is lower than the holding temperature in the heating process.

[0086] The temperature range for soaking in the soaking process is preferably 850°C or higher, and more preferably 900°C or higher. On the other hand, this temperature range is preferably 1080°C or lower, and more preferably 1060°C or lower. Furthermore, the time for soaking in the soaking process is preferably 10 minutes or longer, and more preferably 30 minutes or longer. On the other hand, this time is preferably 10 hours or shorter, and more preferably 5 hours or shorter.

[0087] The atmosphere in the soaking step is not particularly limited, but may be, for example, 95% by volume or more and 100% by volume or less of hydrogen with a dew point of -50°C or more and 0°C or less.

[0088] It is believed that the above-mentioned soaking process favorably balances the Zn concentration diffused in the surface layer region of the base steel sheet during the heating process with the Zn concentration inside the base steel sheet, thereby realizing the above-mentioned Zn concentration gradient in the base steel sheet. At the same time, it is believed that the above-mentioned Al concentration gradient in the base steel sheet can be realized.

[0089] [Cooling process] In the cooling process of the finish annealing step, the steel sheet after the soaking process may be cooled to a temperature range of room temperature to 400°C at an average cooling rate of 0.1°C / min to 10°C / min. The average cooling rate means the value obtained by dividing the temperature from the soaking temperature to 400°C by the cooling time from the soaking temperature to 400°C.

[0090] The average cooling rate during the cooling process is preferably 0.3°C / min or more, more preferably 0.5°C / min or more. Meanwhile, this average cooling rate is preferably 5°C / min or less, more preferably 3°C / min or less. Furthermore, the temperature range during the cooling process is preferably 100°C or more, more preferably 150°C or more. Meanwhile, this temperature range is preferably 370°C or less, more preferably 350°C or less.

[0091] If the average cooling rate during the cooling process is slower than the above range, or if the cooling temperature range during the cooling process is higher than the above range, the Zn concentration gradient in the base steel plate, which was controlled up to the soaking process, may be disturbed during the cooling process.

[0092] [Hot-rolled sheet annealing process] The method for producing a non-oriented electrical steel sheet according to the present embodiment may include a hot-rolled sheet annealing step after the hot rolling step. By carrying out the hot-rolled sheet annealing, preferable magnetic properties can be obtained. This hot-rolled sheet annealing may be a heat retention treatment in which the hot-rolled steel sheet is kept at a temperature during cooling after hot rolling.

[0093] The conditions for the hot-rolled sheet annealing are not particularly limited and may be known conditions. For example, when box annealing is performed, it is preferable to hold the sheet in a temperature range of 700° C. to 900° C. for 60 minutes to 20 hours. When continuous annealing is performed, it is preferable to hold the sheet in a temperature range of 900° C. to 1100° C. for 1 second to 180 seconds.

[0094] [Pickling process] The method for producing a non-oriented electrical steel sheet according to the present embodiment may include a pickling step after the hot rolling step or the hot-rolled sheet annealing step. The pickling step may remove scale formed on the surface of the steel sheet. The pickling conditions are not particularly limited and may be known conditions.

[0095] [Film formation process] The method for producing a non-oriented electrical steel sheet according to this embodiment may include a coating formation step after the finish annealing step. In the coating formation step, the steel sheet after the finish annealing step may be subjected to a coating formation process and, if necessary, an annealing process.

[0096] [Film formation process] The film formation conditions are not particularly limited and may be known conditions. For example, an insulating film consisting of only organic components, only inorganic components, or an organic-inorganic composite may be applied to the surface of the steel sheet to form the film. From the viewpoint of reducing the environmental load, an insulating film that does not contain chromium may be formed. The film formation process may also be a process of applying an insulating coating that exhibits adhesive properties by heating and pressing. Coating materials that exhibit adhesive properties include acrylic resins, phenolic resins, epoxy resins, and melamine resins.

[0097] [Annealing process] In the annealing process, the steel sheet may be held at a temperature in the range of 750° C. to 850° C. for 30 minutes to 150 minutes. The steel sheet subjected to the annealing process may be either a steel sheet after a coating process or a steel sheet that has been subjected to a punching process or other process to give a shape for forming an iron core after the coating process.

[0098] The temperature range maintained during the annealing process is preferably 760°C or higher, and more preferably 770°C or higher. On the other hand, this temperature range is preferably 840°C or lower, and more preferably 830°C or lower. Furthermore, the time maintained within the above temperature range during the annealing process is preferably 45 minutes or longer, and more preferably 60 minutes or longer. On the other hand, this time is preferably 135 minutes or shorter, and more preferably 120 minutes or shorter.

[0099] This annealing process removes residual strain in the steel, recrystallizes the steel, and may grow the crystal grains to a preferred grain size. Note that the steel sheet after the annealing process according to this embodiment maintains the concentration gradient of each element formed before the annealing process.

[0100] The atmosphere in the annealing process is not particularly limited. For example, the atmosphere in the annealing process may be a nitrogen atmosphere, a hydrogen atmosphere, or a mixed atmosphere of nitrogen and hydrogen. The dew point of the atmosphere in the annealing process is preferably -50°C or higher, more preferably -40°C or higher. On the other hand, the dew point is preferably 0°C or lower, more preferably -10°C or lower.

[0101] [Iron core] The iron core according to the present embodiment may include the above-mentioned non-oriented electromagnetic steel sheet. More specifically, the iron core may be a laminated body formed by stacking and integrating non-oriented electromagnetic steel sheets having the above-mentioned characteristics and a shape for forming the iron core. The iron core according to the present embodiment may be an integral punched core or a split core.

[0102] [Manufacturing method of iron core] The manufacturing method of the iron core according to this embodiment may include a step of stacking the non-oriented electromagnetic steel sheets described above. More specifically, the manufacturing method of the iron core may include a stacking step of stacking and integrating non-oriented electromagnetic steel sheets having the above-mentioned characteristics and a shape for forming the iron core. The number of stacked non-oriented electromagnetic steel sheets and the stacking conditions may be adjusted according to the purpose.

[0103] In addition, when the steel plate to be used in the method for manufacturing an iron core according to this embodiment does not have a shape for forming an iron core, a punching process may be performed before the lamination process to obtain a punched member by punching the steel plate. The punched shape and punching conditions of the steel plate may be adjusted according to the purpose.

[0104] Furthermore, the method for manufacturing an iron core according to this embodiment may include a stress relief annealing step after the above punching step or after the above lamination step.

[0105] When the stress relief annealing step is performed in the manufacturing method of the iron core according to the present embodiment, the annealing step of the coating step may be omitted in the manufacturing method of the non-oriented electrical steel sheet described above. For example, the steel sheet after the above-mentioned finish annealing step may be subjected to the coating step of the coating step, and the steel sheet after the coating step may be subjected to the punching step without being subjected to the annealing step of the coating step, and the punched member may be subjected to the lamination step. Then, the stress relief annealing step may be performed after the punching step or the lamination step.

[0106] This stress relief annealing process removes residual strain in the steel, and may also recrystallize the steel and grow the crystal grains to a desired grain size.

[0107] In the stress relief annealing step, the punched member or the laminate may be held at a temperature in the range of 750°C to 850°C for 30 minutes to 150 minutes. The atmosphere in the stress relief annealing step is not particularly limited. For example, the atmosphere in the stress relief annealing step may be a nitrogen atmosphere, a hydrogen atmosphere, or a mixed atmosphere of nitrogen and hydrogen. The dew point of the atmosphere in the stress relief annealing step may be -50 to 0°C.

[0108] [Motor] The motor according to this embodiment may include the above-mentioned iron core. More specifically, the motor mainly includes a stator, a rotor, bearings, a bracket, and lead wires, and the motor according to this embodiment may include the above-mentioned iron core as the iron core of the stator or rotor. The motor according to this embodiment is preferably a drive motor for a hybrid drive vehicle or an electric vehicle, and is preferably a PM motor such as an IPM motor or an SPM motor.

[0109] [Motor manufacturing method] The manufacturing method of the motor according to this embodiment may include a step of laminating the above-mentioned non-oriented electromagnetic steel sheets to obtain an iron core, and a step of assembling this iron core to obtain a motor. More specifically, the manufacturing method of this motor may include a lamination step of laminating non-oriented electromagnetic steel sheets having the above-mentioned characteristics and a shape for forming an iron core to obtain an iron core, and an assembly step of assembling this iron core as a stator core or a rotor core to obtain a motor. The number of layers of the non-oriented electromagnetic steel sheets, the lamination conditions, and the assembly conditions of the iron core may be adjusted according to the purpose.

[0110] As in the above-described method for manufacturing an iron core, if the steel plate used in the method for manufacturing a motor according to this embodiment does not have a shape for forming an iron core, a punching step may be included before the lamination step, in which the steel plate is punched to obtain a punched member. The punched shape and punching conditions of the steel plate may be adjusted according to the purpose.

[0111] Furthermore, similarly to the above-described method for manufacturing the iron core, the method for manufacturing the motor according to this embodiment may include a stress relief annealing step after the punching step or after the lamination step. When this stress relief annealing step is performed, the annealing step of the coating formation step may be omitted in the above-described method for manufacturing the non-oriented electrical steel sheet. The stress relief annealing conditions in the method for manufacturing the motor according to this embodiment may be the same as the stress relief annealing conditions in the above-described method for manufacturing the iron core. EXAMPLES

[0112] The effects of one aspect of the present invention will be explained in more detail by way of examples, but the conditions in the examples are merely examples of conditions adopted to confirm the feasibility and effects of the present invention, and the present invention is not limited to these examples. Various conditions may be adopted in the present invention as long as they do not deviate from the gist of the present invention and the object of the present invention is achieved. The present invention will be explained in detail below by way of examples of the present invention and comparative examples.

[0113] Non-oriented electrical steel sheets were manufactured by carrying out each process under the conditions shown in Tables 17 to 21 using slabs having the chemical compositions shown in Tables 1 to 6. In each manufacturing process, pickling was performed after hot rolling or after hot-rolled sheet annealing, and after cold rolling, a ZnAl alloy was plated on the steel sheet, and an insulating coating was formed after finish annealing. As the insulating coating, an organic-inorganic composite coating containing mainly inorganic components and resin was formed on the steel sheet.

[0114] The base steel sheet of the manufactured non-oriented electrical steel sheet was measured for sheet thickness, Zn concentration gradient, Al concentration gradient, The chemical composition, average crystal grain size, etc. were measured. The measurement methods are as described above. The measurement results are shown in Tables 7 to 16 and Tables 22 to 26. In the tables, elements marked with "-" indicate that no conscious control or manufacturing was performed. Furthermore, manufacturing conditions marked with "-" in the tables indicate that no control was performed. Furthermore, the "surface region" shown in the tables corresponds to the region from the surface of the base steel sheet to 1 / 10 of the sheet thickness. Furthermore, the sheet thickness of the base steel sheet of the manufactured non-oriented electrical steel sheet was the same as the sheet thickness of the steel sheet after the cold rolling process.

[0115] The magnetic flux density, core loss characteristics, and punchability of the produced non-oriented electrical steel sheets were evaluated.

[0116] The magnetic flux density and core loss characteristics were evaluated based on the Single Sheet Tester (SST) defined in JIS C 2556:2015 using steel sheets subjected to the annealing process (800°C for 60 minutes) after the above-mentioned coating process. Note that instead of taking test pieces of the size defined in JIS, smaller test pieces, for example, test pieces of width 55 mm x length 55 mm, may be taken and measurements based on the Single Sheet Magnetic Property Tester. In addition, if a test piece of width 55 mm x length 55 mm cannot be taken, two test pieces of width 8 mm x length 16 mm may be used to make a test piece of width 16 mm x length 16 mm, and measurements based on the Single Sheet Magnetic Property Tester may be performed. In this case, the Epstein equivalent value converted to the measurement value using the Epstein tester defined in JIS C 2550:2011 may be used.

[0117] The magnetic flux density in the rolling direction when the steel sheet is magnetized with a magnetizing force of 5000 A / m is B. 50 The magnetic flux density B is measured in Tesla (T). 50 In addition, the iron loss characteristic was determined as being acceptable when the steel sheet was magnetized at a magnetic flux density of 1.5 T at 50 Hz, and the iron loss W 15 / 50 (commercial frequency iron loss), and iron loss W in the rolling direction when the steel sheet is magnetized at 1 kHz with a magnetic flux density of 1.0 T 10 / 1k (High frequency iron loss) was measured and calculated in units of W / kg. Iron loss W 15 / 50 is 2.20W / kg or less, and the iron loss W 10 / 1k However, it was judged to pass if it was 33W / kg or less.

[0118] The punchability was evaluated by punching a 5 mm circular mold with a steel die using a steel sheet that had been subjected to the above-mentioned coating formation process but not the annealing process, and measuring the burr height. The clearance was 6% of the sheet thickness, and punching was performed using quick-drying oil. A specimen was deemed to have passed the test when the number of punches required to reach a burr height of 50 μm or more was 500,000 or more.

[0119] As shown in Tables 1 to 31, among Test Nos. 1 to 108, the inventive examples were all excellent in magnetic flux density, core loss characteristics, and punchability as non-oriented electrical steel sheets. On the other hand, among Test Nos. 1 to 108, the comparative examples were not excellent in at least one of magnetic flux density, core loss characteristics, and punchability.

[0120] Next, a non-oriented electromagnetic steel sheet that had been subjected to the coating process but not the annealing process was punched, and the punched members were laminated to manufacture an iron core. The manufactured iron core contained the above-mentioned non-oriented electromagnetic steel sheet. The manufactured iron core was also subjected to stress relief annealing, and the iron core was used as a stator core or a rotor core to be assembled to manufacture a motor. The manufactured motor contained the above-mentioned iron core. In the above-mentioned stress relief annealing, the iron core was held at a temperature range of 750°C to 850°C for 30 minutes to 150 minutes.

[0121] The manufactured motor was connected to a load motor via a torque sensor (MAGTROL TM308). The manufactured motor was driven by supplying three-phase AC current from an inverter. The current and voltage supplied from the inverter were measured with a power meter (Yokogawa Electric Model WT1804E) and used as the input. From the torque T (unit: N m) measured by the torque sensor and the rotation speed N (rpm), 2πTN / 60 = output (W) was calculated. Efficiency (%) was calculated as output / input x 100. The manufactured cores and motors had excellent torque characteristics and energy efficiency when using the non-oriented electrical steel sheets that were examples of the present invention among the above-mentioned Test Nos. 1 to 108. On the other hand, the manufactured cores and motors had poor torque characteristics and energy efficiency when using the non-oriented electrical steel sheets that were comparative examples among the above-mentioned Test Nos. 1 to 108.

[0122] [Table 1]

[0123] [Table 2]

[0124]

Table 3

[0125]

Table 4

[0126]

Table 5

[0127]

Table 6

[0128]

Table 7

[0129]

Table 8

[0130]

Table 9

[0131]

Table 10

[0132]

Table 11

[0133]

Table 12

[0134]

Table 13

[0135]

Table 14

[0136]

Table 15

[0137]

Table 16

[0138]

Table 17

[0139]

Table 18

[0140]

Table 19

[0141]

Table 20

[0142]

Table 21

[0143]

Table 22

[0144]

Table 23

[0145] [Table 24]

[0146] [Table 25]

[0147] [Table 26]

[0148] [Table 27]

[0149] [Table 28]

[0150] [Table 29]

[0151] [Table 30]

[0152] [Table 31] [Industrial Applicability]

[0153] According to the above aspects of the present invention, it is possible to provide a non-oriented electrical steel sheet that is excellent in magnetic flux density, iron loss characteristics (commercial frequency iron loss and high frequency iron loss) and punchability. In addition, it is possible to provide an iron core including this non-oriented electrical steel sheet, a method for manufacturing an iron core, and a motor including this iron core, and a method for manufacturing a motor, so that the present invention has high industrial applicability. [Explanation of symbols]

[0154] 1 Non-oriented electrical steel sheet 11 Insulation coating 12 Base steel plate 12a Region from the surface of the base steel plate to 1 / 10 of the plate thickness 12b 1 / 4 of the thickness of the base steel plate 12c 1 / 2 the thickness of the base steel plate

Claims

1. A non-oriented electrical steel sheet having a base steel sheet and an insulating coating, The base steel sheet has a chemical composition, in mass%, Si: 1.0% or more and 5.0% or less, Zn: 0.5% or more and 5.0% or less, Al: 1.0% or more and 6.0% or less, C: 0% or more and 0.0050% or less, Mn: 0% or more and 3.0% or less, P: 0% or more and 0.30% or less, S: 0% or more and 0.010% or less, N: 0% or more and 0.010% or less, Sn: 0% or more and 0.10% or less, Sb: 0% or more and 0.10% or less, Ca: 0% or more and 0.010% or less, Cr: 0% or more and 5.0% or less, Ni: 0% or more and 5.0% or less, Cu: 0% or more and 5.0% or less, Ce: 0% or more and 0.10% or less, B: 0% or more and 0.10% or less, O: 0% or more and 0.10% or less, Mg: 0% or more and 0.10% or less, Ti: 0% or more and 0.10% or less, V: 0% or more and 0.10% or less, Zr: 0% or more and 0.10% or less, Nd: 0% or more and 0.10% or less, Bi: 0% or more and 0.10% or less, W: 0% or more and 0.10% or less, Mo: 0% or more and 0.10% or less, Nb: 0% or more and 0.10% or less, Y: 0% or more and 0.10% or less, with the remainder being Fe and impurities, The thickness of the base steel plate is 0.10 mm or more and 0.35 mm or less, When the base steel plate is viewed on a cut surface whose cutting direction is parallel to the plate thickness direction, The average Zn concentration in the region from the surface of the base steel plate to 1 / 10 of the plate thickness is The Zn concentration is 0.20 mass% or more higher than the Zn concentration at the quarter thickness portion of the plate, and The Zn concentration is 0.40 mass% or more higher than the Zn concentration at the half thickness portion of the plate, The Zn concentration at the quarter thickness portion is The Zn concentration is 0.20 mass% or more higher than the Zn concentration at the plate thickness 1 / 2 part, The average Al concentration in the region from the surface to 1 / 10 of the plate thickness of the base steel plate is The Al concentration is 1.50 mass% or more higher than the Al concentration at 1 / 4 of the plate thickness, and The Al concentration is 3.0 mass% or more higher than the Al concentration at the half thickness portion of the plate, The Al concentration at the quarter thickness portion is The Al concentration is 1.50 mass % or more higher than the Al concentration at the half plate thickness portion. A non-oriented electrical steel sheet.

2. The base steel sheet has a chemical composition, in mass%, Cr: 0.50% or more and 2.0% or less, Contains The non-oriented electrical steel sheet according to claim 1 .

3. An iron core comprising the non-oriented electrical steel sheet according to claim 1 or 2.

4. A method for manufacturing an iron core, comprising a step of stacking the non-oriented electrical steel sheets according to claim 1 or 2.

5. A motor including the iron core according to claim 3.

6. A method for manufacturing a motor, comprising the steps of: laminating the non-oriented electrical steel sheets according to claim 1 to obtain an iron core; and assembling the iron core to obtain a motor.

Citation Information

Patent Citations

  • Silicon steel plate remarkably low in high frequency iron loss

    JP1999293422A

  • Non-oriented electromagnetic steel plate having low high-frequency iron loss and process for producing the non-oriented electromagnetic steel plate

    WO2009072394A1

Cited By

  • Non-oriented silicon steel and preparation method and application thereof

    CN120719204A